ALLOCATIVE EFFICIENCY AS A MANAGERIAL INNOVATION FOR SUSTAINABLE RICE PRODUCTIVITY IN KUPANG REGENCY - Ayu Fitriani; Santhy Chamdra; Putri Manno Raga (Universitas Sebelas Maret, 2026)
Productivity in lowland rice farming within dryland archipelagic regions is often constrained by imprecise input management rather than a lack of technology. Farmers in Kupang Regency typically employ conventional intensification by increasing fertilizer inputs without considering marginal efficiency, leading to cost escalation. This study aims to deconstruct the structure of input usage, analyze allocative inefficiency, and formulate strategies for managerial redesign. A survey was conducted on 80 rice farmers in Noelbaki Village, Central Kupang District, selected using Proportional Random Sampling. Data were analyzed using the Cobb-Douglas production function and the ratio of Marginal Value Product (MVP) to input price. The findings reveal a significant efficiency gap: seeds have an elasticity of 0.418 but are underutilized, while fertilizers have an elasticity of 0.499 but are overutilized. The scale of operation is at decreasing return to scale (0.967). This study recommends reallocating budgets from fertilizer expenditure to high-quality seeds and strengthening farmers' financial literacy as managerial innovations to achieve economic sustainability and food security in East Nusa Tenggara